(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In this article, foreign experiences on the nationalization of new words are studied. In particular, on the example of English, Russian, Kyrgyz languages, this issue was thoroughly researched, and their similarities and differences were analyzed.